Supply chain optimization, design, and management : advances and intelligent methods - Minis, Ioannis (Hershey, PA. : Business Science Reference, 2011)
'This book presents computational intelligence methods for addressing supply chain issues, emphasizing techniques that provide effective solutions to complex supply chain problems and exhibit superior performance to other methods of operations research'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Business logistics; Production control; Operations research; Computational intelligence